SoTL in Human Movement Sciences: Moving Forward in South Africa - Schreck, Cornelia; du Plessis, Alretha; Coetzee, Dané; Bisschoff, Christo; Oosthuizen, Jacobus; Kahts-Kramer, Samantha (Teaching and Learning Inquiry, 2023)
The Scholarship of Teaching and Learning (SoTL) is an emerging focus within South Africa (SA). In Human Movement Sciences (HMS) in SA, research is primarily discipline-specific, and many researchers are unfamiliar with SoTL. To explore how we (as HMS lecturers) could integrate SoTL into our research, we formed a community of practice (CoP). The SoTL unicycle depiction of Swart et al. (2016) suited our visual analogy since the focus of HMS is on the human body that is in motion. For us, the unicycle represented HMS SoTL in motion. Swart et al. (2016) viewed the SoTL movement as an academic’s individual journey, whereas we saw SoTL from a CoP perspective. Therefore, we adapted the unicycle into a tandem bicycle, representing our collaborative engagements. Participatory action learning and action research (PALAR) formed our theoretical framework. Through our dialogue, each tandem wheel’s focus emerged. The back wheel was about deciding to SoTL (or not). This became a linchpin of our critical dialogue during the relationship-building phase of our CoP. Once we committed, we needed to learn how to keep our CoP moving forward. This became the middle wheel of our tandem bicycle. Next, the front wheel and handlebar became our guide into what the future of SoTL would be for us. The tandem bicycle, therefore, represents our collective cycles of learning as we became SoTL researchers. We believe our learning can support others transitioning from discipline-specific research to engaging in SoTL. *Please note that this poster is best viewed in Adobe on a computer/laptop for interactivity. Click here to read the corresponding ISSOTL blog post.